The Relationship between Madrasah Head Leadership with the Teacher's Effectiveness in State MTs 2 Medan - M. Idrus Hasibuan; Nuraini Nuraini (Budapest International Research and Critics University, 2020)
The purpose of this study was to determine (1) How the implementation of madrasa head leadership in MTs Negeri 2 Medan, (2) How the effectiveness of teacher work in MTs Negeri 2 Medan, and (3) The relationship between madrasa head leadership with the effectiveness of teacher work in MTs Negeri 2 Medan . The hypothesis proposed in this study is: